The P-Type ATPase PA1429 Regulates Quorum-Sensing Systems and Bacterial Virulence - Zhang, Yani; Qin, Jing; Tan, Boren; Kong, Weina; Chen, Gukui; Zhang, Chao; Liang, Haihua (Frontiers in Microbiology, 2017)
Pseudomonas aeruginosa is becoming an increasingly prevalent pathogen, capable of causing numerous life threatening infections in immunocompromised patients. The three hierarchically arranged quorum sensing (QS) systems, namely las, rhl and pqs play key roles in coordinating virulence expression in P. aeruginosa. However, the regulatory mechanisms of the pqs system have not been fully elucidated. To identify new genes involved in synthesis of the Pseudomonas quinolone signal (PQS), a transposon mutagenesis library was constructed. PA1429 was found to inhibit PQS biosynthesis. The PA1429 deletion mutant also exhibited increased bacterial motility, biofilm formation, and virulence in a mouse model of acute lung infection. Interestingly, it also displayed reduced tolerance to oxidative stress. Mutated pqsH in the PA1429 deletion background restored bacterial susceptibility to H2O2. In addition, our data showed that PA1429 repressed the expression of las and rhl systems. Overall, these results provide new insights into the complex regulatory networks of quorum-sensing and virulence expression in P. aeruginosa.